ANALISIS PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA LAYANAN SIS N BRO MYBCA YANG DIKELOLA OLEH PT INFOMEDIA NUSANTARA) - Lestari, Intan Puspita; Iskandar, Rhoma (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
In this study, which is based on the Sis N Bro myBCA service run by PT Infomedia Nusantara, examine whether work motivation and job satisfaction concurrently and in part have a substantial impact on employee performance. In this study, multiple linear regression models are used in a quantitative manner. The SPSS 27 program is used for the study's data analysis procedure. The study finds indication that both job satisfaction and work motivation have a significant impact on employee performance, with results showing Fcount Ftable of Fcount 10,837 3,28 Ftable and sig value. 0.000. The results partially demonstrate that the work motivation variable has an impact and is significant on employee performance, with the result value showing tcount 2,576 ttable 2,037